Independensi dan Akuntabilitas Ombudsman Republik Indonesia dengan Instrumen Westminster Foundation for Democracy (WFD) - Ahmad Redi; Mohammad Ryan Bakry (APPTHI, 2018)
Tulisan ini membahas mengenai bagaimana independensi dan akuntabilitas Ombudsman Republik Indonesia (ORI) dalam menjalankan tugasnya terhadap potensi intervensi dari Dewan Perwakilan Rakyat (DPR). Metode yang digunakan yaitu pendekatan kualitatif, dengan teknik pengumpulan data studi kepustakaan, dan teknik analisis data melalui teknik deskriptif analitis kualitatif. Berdasarkan penilaian melalui Instrument Institutional design and governance, Actual autonomy in exercising its mandate dari Westminster Foundation For Democracy (WFD) terdapat beberapa penilaian independensi dan akuntabilitas yang rendah, yaitu pada: (1) sufficiency of financial resources for performing its functions; (2) extent of autonomy to generate its own financial revenues; (3) security and stability of budget during past three years; dan (4) stability of staff and extent of staff turn-over. Ke depan ORI harus memperbaiki beberapa skor rendah independensi dan akuntabilitas dengan relasi kelembagaannya kepada DPR. Abstract This paper discusses the independence and accountability of the Ombudsman of the Republic of Indonesia (ORI) in carrying out their duties regarding potential intervention from the People’s Representative Council (DPR). A method is a qualitative approach, with library research data collection techniques and data analysis techniques through qualitative analytical descriptive techniques. Based on an assessment through the Instrument Institutional design and governance, Actual autonomy in exercising its mandate from the Westminster Foundation For Democracy (WFD), there are several assessments of independence and low accountability, namely on: (1) sufficiency of financial resources for performing its functions; (2) the extent of autonomy to generate its financial revenues; (3) security and stability of the budget during the past three years; and (4) stability of staff and extent of staff turn-over. In the future, ORI must improve several low scores on independence and accountability with its institutional relationship with the DPR. Keywords: Ombudsman of the Republic of Indonesia, independence, accountability, Power, Control